Gas-Sensing Performances of Metal Oxide Nanostructures for Detecting Dissolved Gases: A Mini Review - Guan, Wei; Tang, Na; He, Kuang; Hu, Xiaoying; Li, Mingshan; Li, Kaiming (Frontiers in Chemistry, 2020)
Gas sensor was wildly used in various fields related to people's lives. Gas sensor materials was the core factor that affected the performance of gas sensor, and attracted much attention of scientific researchers due its high sensitivity, high selectivity, adjustable reliability, low cost and other advantages. The preparation of nanostructures with high specific surface area was a useful method to improve the gas sensing performance of metal oxide semiconductor. Meanwhile, lots of research focused on preparing nanostructures with higher specific surface area. This paper showed some fabricated sensor with high sensitivity, good selectivity and long-term stability, making it a promising candidate for toxic gas detection. Besides, this paper reviewed the development status of metal oxides used for gas sensor.